Polymethine dyes based on pyrylium salts with unsaturated cyclic groups in the 4-position - Kurdyukov, V.V.; Tolmachev, A.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
2,6-Diphenyl-substituted pyrylium salts containing unsaturated cyclic groups are synthesized. They are shown to be feasible precursors for the synthesis of symmetric and unsymmetric dyes. The spectral properties of synthesized dyes are studied in solvents of different polarities.